P770 Jarisch-herxheimer reaction in central nervous system among neurosyphilis patients: discontinuation of therapy or not?. (14th July 2019) - Peng, Rui-Rui; Wu, Juan; Zhao, Wei; Zhu, Lin; Lu, Sheng; Gu, Xin; Guan, Zhi-Fang; Zhou, Pingyu
Abstract : Background: Syphilis has returned to china with a vengeance since the 21st century, and the epidemiology of neurosyphilis has largely paralleled that of active syphilis. Prompt therapy with high-dose intravenous benzylpenicillin is critical to alleviate clinical symptoms of neurosyphilis patients. However, patients may experience an exacerbation of mental and/or neurological symptoms following the initiation of treatment due to a severe Jarisch-Herxheimer reaction (JHR) in central nervous system (CNS). We retrospectively analyzed the incidence, risk factors and prognosis for JHR in CNS in Shanghai Skin Disease Hospital, China. Methods: From July 1, 2017 to December 31, 2018 at our sexually transmitted disease ward, 574 neurosyphilis patients received the high-dose intravenous benzylpenicillin. Patient factors were recorded, including age, gender, neurosyphilis type, serum and cerebrospinal fluid-venereal disease research laboratory test (CSF-VDRL) titer, white blood cell count and protein level of CSF, accompanying symptoms, clinical management and prognosis. Results: All patients were HIV negative. The total incidence of JHR in CNS was 7.14% (41/574, 95% CI: 5.23–9.65%), being the most frequent among patients with general paresis. The mean timing of JHR after the initial dose of benzylpenicillin was to start at 6 hours (range: 0.5–13), peak at 8 hours (range: 0.5–20), and subside by 17 hours (range: 10–30). Besides fever and chills, the main symptoms were hallucination, paranoia, aggressive behavior, mental depression, cognitive impairment, confusion, urinary incontinence, stupor, convulsion and seizures in descending order. The JHR was significantly related to higher CSF-VDRL titer, pleocytosis, no usage of antibiotics in the last 6 months ( p <0.05). The therapy was stopped with a resolution of seizures in two patients. However, benzylpenicillin was reinstituted uneventfully 3 days later. Conclusion: Higher CSF-VDRL titer, pleocytosis and no recent usage of antibiotics were associated with an increased risk for JHR in CNS. Therapy of neurosyphilis can be continued with intensive surveillance. Disclosure: No significant relationships.